Assessment of genetically modified oilseed rape MS8, RF3 and MS8 × RF3 for renewal authorisation under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐RX‐024) - EFSA Panel on Genetically Modified Organisms (GMO); Ewen Mullins; Jean Louis Bresson; Tamas Dalmay; Ian Crawford Dewhurst; Michelle M Epstein; Leslie George Firbank; Philippe Guerche; Jan Hejatko; Francisco Javier Moreno; Hanspeter Naegeli; Fabien Nogué; et al. (EFSA Journal)
Abstract Following the submission of application EFSA‐GMO‐RX‐024 under Regulation (EC) No 1829/2003 from BASF Agricultural Solutions Seed US LLC, the Panel on Genetically Modified Organisms of EFSA was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application for the herbicide tolerant genetically modified oilseed rape MS8, RF3 and MS8 × RF3, for food and feed uses, excluding cultivation within the European Union. The data received in the context of this renewal application contained post‐market environmental monitoring reports, a systematic search and evaluation of literature, updated bioinformatic analyses, and additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequences of the events in oilseed rape MS8, RF3 and MS8 × RF3 considered for renewal are identical to the sequences of the originally assessed events, the GMO Panel concludes that there is no evidence in renewal application EFSA‐GMO‐RX‐024 for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on oilseed rape MS8, RF3 and MS8 × RF3.